2017
DOI: 10.1101/198283
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Root type and soil phosphate determine the taxonomic landscape of colonizing fungi and the transcriptome of field-grown maize roots

Abstract: Key findingOur data illustrates for the first time that root type identity and phosphate availability determine the community composition of colonizing fungi and shape the transcriptomic response of the maize root system.SummaryPlant root systems consist of different root types colonized by a myriad of soil microorganisms including fungi, which influence plant health and performance. The distinct functional and metabolic characteristics of these root types may influence root type inhabiting fungal communities.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Interactions between roots and their rhizosphere microbiota are essential for plant growth and performance 7,8 . It is known that dynamic patterns of the root transcriptome synchronize with distinct microbial taxa colonizing different root types 26,27 . However, numerous scenarios and mechanisms by which microbes modulate plant development are still unknown especially in crops 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interactions between roots and their rhizosphere microbiota are essential for plant growth and performance 7,8 . It is known that dynamic patterns of the root transcriptome synchronize with distinct microbial taxa colonizing different root types 26,27 . However, numerous scenarios and mechanisms by which microbes modulate plant development are still unknown especially in crops 44 .…”
Section: Discussionmentioning
confidence: 99%
“…The great architectural and functional diversity of the maize root system has the potential to shape the rhizosphere microbiota composition 25 . Specifically, root type-specific metabolic properties influence microbial communities inhabiting respective root types in maize and rice [26][27][28] . Conversely, it has been suggested that rootassociated bacteria contribute to differential nitrogen use efficiencies observed in indica and japonica rice varieties 29 , suggesting that root microbiota could alleviate overall nutrient stress in crops.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively few studies have investigated spatial microbiome dynamics within organs, even fewer while also considering host genotype. In maize, fungal colonization differed between axial and lateral roots, corresponding to physiological and transcriptional differences (Yu et al ., 2018). Similarly, Avena fatua rhizosphere communities varied in density and composition along the length of individual roots, matching spatial patterns in exudate content (DeAngelis et al ., 2009).…”
Section: Microbiome Heritability Across Plant Anatomical Compartmentsmentioning
confidence: 99%
“…Drought-induced expression changes that were tied to fitness under drought suggested that plants may respond adaptively to water limitation and concomitant P deficiency by intensifying interactions with AM fungi. Our hypothesis based on these patterns and on previous studies of plant relations with AM fungi (Colard et al, 2011; Lanfranco et al, 2018; Mbodj et al, 2018; Yu et al, 2018), that interactions with AM fungi could have positive fitness consequences under drought, held up in the next dry season. We found that root interactions with AM fungi were positively linked with straw biomass, an important fitness component, within dry as well as between wet and dry field conditions.…”
Section: Discussionmentioning
confidence: 75%
“…Two published examples provide excellent insights that are extended by our study. In the first, Yu and colleagues measured gene expression in roots of field-grown maize at high and low soil phosphate levels, observing that genes involved in signaling and cell wall metabolism were particularly responsive (Yu et al, 2018). In the second, Kawakatsu and co-workers measured gene expression in both the roots and shoots of a panel of diverse rice accessions grown in relatively dry upland growth conditions (Kawakatsu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%